Development of Self‐Aligned Top‐Gate Transistor Arrays on Wafer‐Scale Two‐Dimensional Semiconductor - Yuxuan Zhu; Jinshu Zhang; Hui Xie; Yin Xia; Xiangqi Dong; Saifei Gou; Zhejia Zhang; Xinliu He; Haojie Chen; Mingrui Ao; Qicheng Sun; Yan Hu; et al. (Advanced Science)
Abstract Two‐dimensional semiconductor materials (2DSM) effectively mitigate the short‐channel effect due to their atomic thickness, offering significant advantages over traditional silicon‐based materials, particularly in short channel length. In manufacturing 2DSM top‐gate field‐effect transistors (TG‐FETs), simultaneous miniaturization of the gate and channel can only be achieved through a self‐alignment process, enabling high‐density integration of short‐channel FETs. However, current self‐aligned FETs based on 2DSM face challenges in attaining wafer‐scale integration due to manufacturing process limitations. This work has successfully developed high‐performance and wafer‐scale TG‐FET arrays using a self‐aligned method that integrates the processes of dry etching, wet selective etching, and post‐device optimization. The miniaturization is demonstrated by fabricating TG‐FETs with a channel length of 200 nm, achieving an impressive on‐state current density of 465.5 µA µm−1 and a high on‐off current ratio of 108. Furthermore, we constructed the inverters and logic modules based on self‐aligned FETs, showcasing the process's compatibility for future integration.